Deuterated Polyunsaturated Fatty Acids Reduce Oxidative Stress and Extend the Lifespan of C. elegans - Beaudoin-Chabot, Caroline; Wang, Lei; Smarun, Alexey V.; Vidović, Dragoslav; Shchepinov, Mikhail S.; Thibault, Guillaume (Frontiers in Physiology, 2019)
Chemically reinforced essential fatty acids promise to flight numerous age-related diseases including Alzheimer’s, Friedreich’s ataxia and other neurological conditions. The reinforcement is achieved by substituting the atoms of hydrogen at the bis-allylic methylene of these essential fatty acids with the isotope deuterium. This substitution leads to stronger chemical bonds and, hence, the prevention of substantial chemical damage. This approach has the advantage of preventing the harmful accumulation of reactive oxygen species (ROS) by inhibiting the propagation of lipid peroxidation while antioxidants potentially neutralise beneficial oxidative species. Here, we developed a model system to mimic the human dietary requirement of omega-3 in C. elegans to study the role of deuterated polyunsaturated fatty acids (D-PUFAs). Deuterated trilinolenin [D-TG(54:9)] was sufficient to prevent the accumulation of lipid peroxides and to reduce the accumulation or ROS. Moreover, D-TG(54:9) significantly extended the lifespan of worms under normal and oxidative stress conditions. These findings suggest that D-PUFAs can be used as a food supplement to decelerate the aging process, resulting in extended lifespan.